SIKU Interactive Media: The Development of Learning Media to Improve Student Financial Literacy - Sitorus, Destri Sambara; Sadjiarto, Arief (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to produce an interactive media SIKU that can be used in the Economics learning process as a learning media to improve the students' financial literacy. The research method used is Research and Development (RnD) using the ADDIE development procedure. The data were collected using a questionnaire to obtain quantitative data in the form of an assessment score on the feasibility of the learning media, and qualitative data in the form of comments and suggestions were used to improve the learning media. The data that had been collected were analyzed descriptively. The results of this study indicate that the assessment done by the media expert, subject-matter expert, and also practitioners claimed that this media was feasible and could be used in the learning process. The result of the learning media assessment by the students of SMK Kristen BM Salatiga showed a score of 4.12 in the good category. The assessment score by the students of SMA Negeri 3 Salatiga of 4.36, in the very good category, and the assessment score by students of SMA Kristen Satya Wacana of 3.98 is in the good category. The assessment by students showed that all aspects of the assessment are included in good and very good categories. Thus, it can be concluded that SIKU interactive media is feasible to use in the Economics learning process as a media to improve students' financial literacy.